ABCC5 supports osteoclast formation and promotes breast cancer metastasis to bone - Mourskaia, Anna A (BioMed Central, 2012)
INTRODUCTION: Bone is the most common site of breast cancer metastasis, and complications associated with bone metastases can lead to a significantly decreased patient quality of life. Thus, it is essential to gain a better understanding of the molecular mechanisms that underlie the emergence and growth of breast cancer skeletal metastases. METHODS: To search for novel molecular mediators that influence breast cancer bone metastasis, we generated gene-expression profiles from laser-capture microdissected trephine biopsies of both breast cancer bone metastases and independent primary breast tumors that metastasized to bone. Bioinformatics analysis identified genes that are differentially expressed in breast cancer bone metastases compared with primary, bone-metastatic breast tumors. RESULTS: ABCC5, an ATP-dependent transporter, was found to be overexpressed in breast cancer osseous metastases relative to primary breast tumors. In addition, ABCC5 was significantly upregulated in human and mouse breast cancer cell lines with high bone-metastatic potential. Stable knockdown of ABCC5 substantially reduced bone metastatic burden and osteolytic bone destruction in mice. The decrease in osteolysis was further associated with diminished osteoclast numbers in vivo. Finally, conditioned media from breast cancer cells with reduced ABCC5 expression failed to induce in vitro osteoclastogenesis to the same extent as conditioned media from breast cancer cells expressing ABCC5. CONCLUSIONS: Our data suggest that ABCC5 functions as a mediator of breast cancer skeletal metastasis. ABCC5 expression in breast cancer cells is important for efficient osteoclast-mediated bone resorption. Hence, ABCC5 may be a potential therapeutic target for breast cancer bone metastasis.